In margine al Lazzaretto Vecchio di Venezia. Le scritture epigrafiche di Francesca Malagnini - Rinaldin, Anna (Quaderni Veneti, 2019)
The article is focused on some recent textual and linguistic acquisitions contained in the volume by Francesca Malagnini, Il Lazzaretto Vecchio di Venezia. Le scritture epigrafiche (Venice: Marcianum Press, 2018). In particular, the edited epigraphic writings in Latin and in vernacular are resumed and commented with reference to their different functions. In this context, the importance of the texts that convey the language of use emerges as a fundamental item for the reconstruction of the history of Italian.